Rational design of the solid-state synthesis of materials based on poly-aromatic molecular complexes12. Issue 31 (11th July 2016) - Palin, L.; Conterosito, E.; Caliandro, R.; Boccaleri, E.; Croce, G.; Kumar, S.; van Beek, W.; Milanesio, M.
Abstract : A facile solid-state synthesis method of molecular complexes is proposed. The kinetic is revealed by PCA analysis of in-situ XRPD data. Abstract : The possibility of exploiting a thermally-induced solid-state reaction to obtain the formation of a fluorene and TCNQ molecular complex was proposed by some of us (Kumar et al., Cryst. Growth Des., 2009, 9 (8), 3396–3404). In this paper, we generalize and rationalize the approach to other charge transfer (CT) molecular complexes with naphthalene and anthracene, changing the size of the donor moiety to propose a general approach for the preparation of this class of materials by exploiting the solid-state synthesis method. Moreover, the kinetic features of the solid state reactions were fully elucidated by Raman spectroscopy and high resolution X-ray Powder Diffraction analysis ( in situ Raman/XRPD), exploiting the Avrami equation in isothermal and non-isothermal conditions; rate constants, reaction orders and activation energies were obtained. All the three tested solid-state charge transfer (SS-CT) reactions obeyed a general rule, whereby the most apt reaction temperature was predicted. Finally, a method based on principal component analysis (PCA) for a fast kinetic analysis of in situ XRD synchrotron data was successfully developed, employing a formalism suitable for the analysis of non-isothermal reaction data, thus allowing a high throughput approach for the fast screening of the kinetics of parent reactions. PCA analysis was exploited as an alternative technique to obtain kinetic information in a faster and more efficient way, which can be used for online monitoring and/or in all those cases where Rietveld analysis is not feasible.